2020
DOI: 10.1007/s11738-020-03046-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structural analysis of the Bx6 and Bx7 genes controlling the biosynthesis of benzoxazinoids in rye (Secale cereale L.)

Abstract: Benzoxazinoids (BXs) are plant secondary metabolites, first discovered in the 1950s, which are synthesized in many monocotyledonous species from the Poaceae family and in several dicotyledonous plants. They constitute a significant element of the plant's defence mechanism against both biotic (pests and diseases) and abiotic (elevated salinity, heavy metals) stresses. The aim of this research was to gain more information on the genetic background of BXs biosynthesis in rye (Secale cereale L.) by isolating and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Therefore, elucidating the BXD biosynthesis pathway in wheat is critical for improving the natural mode of defense against herbivores and to ensure food security. In the present study, TtBX6 from cultivated tetraploid wheat and TdBX6 from the wild emmer wheat were identified using sequence similarity to already known BX6 orthologs in maize (Zea mays) [58], rye (Secale cereale), and T. aestivum [27,59,60]. Sequence comparisons showed that S. cereale ScBX6 has a greater similarity with wheat BX6 paralogs [60] than with maize BX6 (Figure 2).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, elucidating the BXD biosynthesis pathway in wheat is critical for improving the natural mode of defense against herbivores and to ensure food security. In the present study, TtBX6 from cultivated tetraploid wheat and TdBX6 from the wild emmer wheat were identified using sequence similarity to already known BX6 orthologs in maize (Zea mays) [58], rye (Secale cereale), and T. aestivum [27,59,60]. Sequence comparisons showed that S. cereale ScBX6 has a greater similarity with wheat BX6 paralogs [60] than with maize BX6 (Figure 2).…”
Section: Discussionmentioning
confidence: 85%
“…The gene IDs of BX6 genes in tetraploid and hexaploid wheat are listed in Supplementary Table S2. To identify further BX6 orthologs/paralogs, the well-characterized BX6 from maize [58] and ScBX6 from rye (Secale cereale) [59,60] were used to conduct a TBLASTN search against the genomes of hexaploid, tetraploid, and other Triticeae species, including T. urartu, a diploid progenitor of the bread wheat A subgenome, and Aegilops tauschii, a diploid progenitor of the bread wheat D subgenome [59]. The progenitor of the B subgenome is yet identified [61], therefore was not included in the analysis.…”
Section: Phylogenetic Analysis Of Wheat Bx6mentioning
confidence: 99%
“…Therefore, elucidating the BXD biosynthesis pathway in wheat is critical for improving the natural mode of defense against herbivores and to ensure food security. In the present study, TtBX6 from cultivated tetraploid wheat and TdBX6 from the wild emmer wheat were identified using sequence similarity to already known BX6 orthologs in maize (Zea mays) [58], rye (Secale cereale), and T. aestivum [27,59,60]. Sequence comparisons showed that S. cereale ScBX6 has a greater similarity with wheat BX6 paralogs [60] than with maize BX6 (Figure 2).…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, TtBX6 from cultivated tetraploid wheat and TdBX6 from the wild emmer wheat were identified using sequence similarity to already known BX6 orthologs in maize (Zea mays) [58], rye (Secale cereale), and T. aestivum [27,59,60]. Sequence comparisons showed that S. cereale ScBX6 has a greater similarity with wheat BX6 paralogs [60] than with maize BX6 (Figure 2). In hexaploid wheat, four TaBX6 genes were identified.…”
Section: Discussionmentioning
confidence: 86%
“…For instance, various species of the Gramineae family with a relatively high concentration of BXDs are resistant to the greenbug [ 49 ]. It has been established by now that the synthesis of BXDs in maize is controlled by 16 genes ( ZmBx1 – ZmBx14 , ZmGlu1 – ZmGlu2 ) [ 50 , 51 ], by 13 in wheat ( TaBx1 – TaBx5 , TaGlu1a – TaGlu1d , TaGT1a – TaGT1d ) [ 52 , 53 ], and by eight ScBx genes in rye [ 54 ]. The plants of Hordeum brachyantherum Nevski, H. flexuosum (Nees ex Steud.)…”
Section: Mechanisms Of Passive (Constitutional) Resistance Of Cereals...mentioning
confidence: 99%